Effect of sodium hypochlorite and peracetic acid on the surface roughness of acrylic resin polymerized by heated water for short and long cycles - Sczepanski, Felipe; Sczepanski, Claudia Roberta Brunnquell; Berger, Sandrine Bittencourt; Consani, Rafael Leonardo Xediek; Gonini-Júnior, Alcides; Guiraldo, Ricardo Danil (European Journal of Dentistry, 2014)
Objective: To evaluate the surface roughness of acrylic resin submitted to chemical disinfection via 1% sodium hypochlorite (NaClO) or 1% peracetic acid (C2H4O3). Materials and Methods: The disc-shaped resin specimens (30 mm diameter ×4 mm height) were polymerized by heated water using two cycles (short cycle: 1 h at 74°C and 30 min at 100°C; conventional long cycle: 9 h at 74°C). The release of substances by these specimens in water solution was also quantified. Specimens were fabricated, divided into four groups (n = 10) depending on the polymerization time and disinfectant. After polishing, the specimens were stored in distilled deionized water. Specimens were immersed in 1% NaClO or 1% C2H4O3 for 30 min, and then were immersed in distilled deionized water for 20 min. The release of C2H4O3 and NaClO was measured via visual colorimetric analysis. Roughness was measured before and after disinfection. Roughness data were subjected to two-way ANOVA and Tukey's test. Results: There was no interaction between polymerization time and disinfectant in influencing the average surface roughness (Ra, P = 0.957). Considering these factors independently, there were significant differences between short and conventional long cycles (P = 0.012), but no significant difference between the disinfectants hypochlorite and C2H4O3 (P = 0.366). Visual colorimetric analysis did not detect release of substances. Conclusion: It was concluded that there was the difference in surface roughness between short and conventional long cycles, and disinfection at acrylic resins polymerized by heated water using a short cycle modified the properties of roughness.
Keywords: Acrylic resins; dental waste; disinfection; polymerization